Pengaruh Metode Pembelajaran Diskusi Berbantukan Internet terhadap Hasil Belajar Mahasiswa - Mawaddah, Hayyatun (Jurnal Kreatif Online, 2020)
The purpose of this study was to describe the effect of internet-based discussion method learning on student learning outcomes in the low plant botanical course (BTR) Biology Education Study Program for the 2016/2017 academic year. This research was quasy experiment or quasi-experimental. The experimental design used a posttest only-non-equivalent control group design. The study population was students who programmed the BTR course in the odd semester of 2016/2017 which consisted of 4 study groups. The research sample was class D with 40 students as the treatment group and class B with 39 students as the comparison group. Data was analyzed by statistical parametric using t-test assisted by the application of the SPSS 18 program. The average posttest score for treatment group 1 (Î¼1) was 79.62, higher than the average posttest score for the comparison class (Î¼2), which was 59.00. It revealed that H0 was rejected and H1 was accepted, which means that there was an effect of internet-based discussion learning on student learning outcomes in the BTR course in the Biology Education Study Program for the 2016/2017 academic year.